Individual fate and gut microbiome composition in the European wild rabbit (Oryctolagus cuniculus) - Gerard Funosas (Nature Portfolio, 2021)
Abstract Studies connecting microbiome composition and functional performance in wildlife have received little attention and understanding their connections with wildlife physical condition are sorely needed. We studied the variation in gut microbiota (hard fecal pellets) between allopatric subspecies of the European wild rabbit in wild populations and in captured individuals studied under captivity. We evaluated the influence of environmental and host-specific factors. The microbiome of wild rabbit populations reduced its heterogeneity under controlled conditions. None of the host-specific factors tested correlated with the microbiota composition. We only observed significant intra-group dispersion for the age factor. The most diverse microbiomes were rich in Ruminococcaceae potentially holding an enriched functional profile with dominance of cellulases and xylanases, and suggesting higher efficiency in the digestion of fiber-rich food. Conversely, low diversity gut microbiomes showed dominance of Enterobacteriaceae potentially rich in amylases. We preliminary noticed geographical variations in field populations with higher dominance of Ruminococcaceae in south-western than in north-eastern Spain. Spatial differences appeared not to be subspecies driven, since they were lost in captivity, but environmentally driven, although differences in social structure and behavior may also play a role that deserve further investigations. A marginally significant relationship between the Ruminococcaceae/Enterobacteriaceae ratio and potential life expectancy was observed in captive rabbits. We hypothesize that the gut microbiome may determine the efficiency of feeding resource exploitation, and can also be a potential proxy for life expectancy, with potential applications for the management of declining wild herbivorous populations. Such hypotheses remain to be explored in the future.